2021
DOI: 10.1021/acs.jpcc.1c03331
|View full text |Cite
|
Sign up to set email alerts
|

Surface Photoluminescence of Oxidized Nanodiamonds: Influence of Environment pH

Abstract: Nanoparticles’ environment, in particular pH, can strongly affect their photoluminescence (PL). This can be especially true for the surface PL of nanodiamonds (NDs) known to be dependent on the composition of surface groups. In this paper, the effect of environmental pH in the range from 2 to 12.5 on the surface photoluminescence of oxidized NDs of various syntheses and surface treatments was investigated. For the first time, the varying changes of the NDs’ PL with the pH were shown, having, however, an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 85 publications
(175 reference statements)
2
8
0
Order By: Relevance
“…According to the authors of [28], this phenomenon may be a consequence of the fact that the energy of triplet excitation (T 3 ) of the deprotonated form is located slightly below the energy of its singlet state (S 1 ), which makes the speed on interlevel transition from S 2 to T 3 higher in the protonated form than in the deprotonated form. Also, it should be noted that results obtained in this study for the effect of pH on the PL of several types of CD in water are fully compatible with results of similar studies for water suspensions of detonation-synthesized nanodiamonds having large amount of s p 2 -hybridized carbon on their surfaces [29]. In the above-mentioned study confirmed by quantum-chemical methods the hypothesis that the obtained dependence of PL of the s p 2 -hybridized carbon on the environment pH is caused by protonation/deprotonation processes.…”
Section: Pl-spectroscopysupporting
confidence: 89%
“…According to the authors of [28], this phenomenon may be a consequence of the fact that the energy of triplet excitation (T 3 ) of the deprotonated form is located slightly below the energy of its singlet state (S 1 ), which makes the speed on interlevel transition from S 2 to T 3 higher in the protonated form than in the deprotonated form. Also, it should be noted that results obtained in this study for the effect of pH on the PL of several types of CD in water are fully compatible with results of similar studies for water suspensions of detonation-synthesized nanodiamonds having large amount of s p 2 -hybridized carbon on their surfaces [29]. In the above-mentioned study confirmed by quantum-chemical methods the hypothesis that the obtained dependence of PL of the s p 2 -hybridized carbon on the environment pH is caused by protonation/deprotonation processes.…”
Section: Pl-spectroscopysupporting
confidence: 89%
“…It was previously shown that the main reason for the change of photoluminescence of CDs obtained by hydrothermal synthesis with the change of pH of the solution, , similar to other carbon nanoparticles–nanodiamonds, is (de)­protonation of surface groups. Deprotonation of surface groups occurs in the pH range from p K a – 1 to p K a + 1, where p K a is the decimal logarithm of the acid (or alkaline) K a index of certain surface groups.…”
Section: Resultsmentioning
confidence: 95%
“…This means that small aggregation of nanoparticles occurs in water due to the interaction of richly developed surface groups of various nanoparticles with each other. It should be noted that three types of the main chemically active functional groups on the surface of CDs (carboxyl, hydroxyl and amide) at the specified measured pH value are in different states: carboxyl groups are deprotonated (−COO – ), hydroxyl groups are neutral (−OH), amide groups on sp 2 - and sp 3 -hybridized bases are excessively protonated (−NH 3 + ) and neutral (−NH 2 ), respectively , (for more details, see section ). It is most likely that the negative zeta potential of CDs is caused by the quantitative advantage of deprotonated carboxyl groups over positively charged groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the photoluminescence and applications of fullerenes, CNOs, and NDs are usually limited owing to blue emissions, low QYs, and short Stokes shifts. 303,382 However, oxidation with strong acids; surface passivation by inserting carboxyl, amino, and hydroxyl groups; and covalent surface functionalization by conjugation with fluorescent molecules and specific recognition markers are convenient and effective approaches for improving fluorescent properties endowing biological diagnosing, tracking, and imaging capabilities for fabricating fascinating fullerenes, CNOs, and NDs sensors. 267,322,383,384 Owing to their excellent photoluminescence and multicolor fluorescence emission, which mainly originates from quantum confinement and surface defects, CDs fluorescent properties have attracted widespread interest.…”
Section: Properties Of 0d Cnms Applied In Fluorescent Sensing and Ima...mentioning
confidence: 99%
“…For 0D CNMs, photoluminescence is the most interesting property, has attracted the most attention, and is how we discovered 0D CNMs for applications. , Similar to pristine fullerenes, pristine CNOs and NDs sometimes exhibit low fluorescence efficiencies and stabilities and poor sensitivities and water solubilities. Therefore, the photoluminescence and applications of fullerenes, CNOs, and NDs are usually limited owing to blue emissions, low QYs, and short Stokes shifts. , However, oxidation with strong acids; surface passivation by inserting carboxyl, amino, and hydroxyl groups; and covalent surface functionalization by conjugation with fluorescent molecules and specific recognition markers are convenient and effective approaches for improving fluorescent properties endowing biological diagnosing, tracking, and imaging capabilities for fabricating fascinating fullerenes, CNOs, and NDs sensors. ,,, …”
Section: Optical Properties Of 0d Cnmsmentioning
confidence: 99%